The determinants of pornography actress production. Issue 20 (28th November 2017) - Wang, Shinn-Shyr; Chou, Li-Chen
ABSTRACT: This study investigates empirically the influences of physical appearances and risky sex in the production of adult video (AV) actresses. By analysing data concerning the Japanese AV actresses whose careers commenced between 2002 and 2013, we found that significant increases in the number of video shots of actresses are brought by cup sizes, working experiences, experiences as models or entertainers, and acting in videos of risky sex, but acting in risky sex videos has no significant influence on the production of those with greater cup sizes or serving as models or entertainers. We interpret that these actresses attract the market attention by their favoured appearances, and thus have no incentives to raise their production by acting in risky sex videos.